2016
DOI: 10.1080/17290376.2016.1226942
|View full text |Cite
|
Sign up to set email alerts
|

HIV status disclosure rate and reasons for non-disclosure among infected children and adolescents in Enugu, southeast Nigeria

Abstract: Aims: To determine the rate of HIV status disclosure, caregivers’ reasons for non-disclosure, and factors influencing disclosure among a sample of HIV-infected children in Enugu, southeast Nigeria. Methods: Data were collected prospectively via a questionnaire on HIV-infected children and their caregivers who visited the pediatric HIV clinic of the University of Nigeria Teaching Hospital between July 1, 2012, and June 30, 2013. The data analysis was performed using Statistical Package for the Social Sciences v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
(24 reference statements)
6
11
3
Order By: Relevance
“…In contrast to other reports, [20,26] girls were 1.45 times more likely than boys to have been disclosed their HIV positive status. This quantitative finding was corroborated by the qualitative component of our study where caregivers shared their views that female children tend to attain 'maturity' earlier than their male counterparts and would therefore be better equipped to cope with the news, thus, explaining the higher likelihood of disclosure to female children in our study setting.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In contrast to other reports, [20,26] girls were 1.45 times more likely than boys to have been disclosed their HIV positive status. This quantitative finding was corroborated by the qualitative component of our study where caregivers shared their views that female children tend to attain 'maturity' earlier than their male counterparts and would therefore be better equipped to cope with the news, thus, explaining the higher likelihood of disclosure to female children in our study setting.…”
Section: Discussioncontrasting
confidence: 93%
“…For example, most children studied in the earlier report were pre-adolescent (mean age 8.8 ± 2.2 years) compared to our study in which the majority were in early and mid-adolescence (mean age 12.2 ± 3.2 years), making disclosure more likely in our study with corresponding higher prevalence. More recent studies in Nigeria by Ubesie et al, [20] and Odiachi et al [21] reported prevalence of disclosure to HIV positive children of 29.5 and 30.9% respectively; comparable to our findings which suggests an increase prevalence of disclosure to Nigerian children living with HIV within recent time. Although relatively higher than most reports from within Nigeria and the African continent, [5,[22][23][24][25][26][27][28] our disclosure rate are lower compared with findings from the US, Canada and Europe [29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…The mean age of HIV disclosure was found to be 12.48± 2.46 years in index study. This was rather late when compared to nine years reported by Mialky et al 14 but similar to 11.52 ±2.25 years reported by Ubesie et al 17 . Studies show that early disclose of HIV status like most chronic illnesses improves self esteem, reduces the risk to fantasies about illness and improves access to care and support.…”
Section: Discussionsupporting
confidence: 44%
“…Similar findings have been reported earlier [ 11 14 ]. This could be explained by caregivers' belief that younger children are not mature enough to understand the disease [ 15 , 16 ] and by the age of 10 years and above parents gain the confidence to disclose HIV status. On the other hand, it takes a time for the provider to build strong trust with the guardians and the child and therefore delaying the time for status disclosure.…”
Section: Discussionmentioning
confidence: 99%